A cytological study on peripheral lymphadenopathy in a tertiary care center with special reference to tuberculous lymphadenitis - Sanjuna Dharmalingam; Suresh Kumar Sutrakar; Jatav, Jagannath; Verma, Sadhana (Asian Journal of Medical Sciences, 2022)
Background: Fine-needle aspiration cytology (FNAC) is the most common, cost-effective, and time-efficient cytological diagnostic procedure and is used routinely in cases of swelling or lymph node enlargement at accessible sites. FNAC plays an important role in diagnosing benign and malignant lesions of peripheral lymphadenopathy cases and also provides a valuable screening test. Aims and Objectives: In this study, we aimed to evaluate various cytomorphological manifestations of lymphadenopathies and the suggestive cases of tuberculous lymphadenitis were divided based on their cytomorphological patterns. Materials and Methods: The current prospective study was conducted in the Department of Pathology, SSMC, Rewa, M.P. A total of 150 cases of peripheral lymphadenopathy were subjected to FNAC and were categorized based on their cytological findings. The cases which showed features suggestive of tuberculous lymphadenitis were further categorized into four distinct cytological patterns (I to IV). Results: Out of 150 cases of peripheral lymphadenopathies, the most common lesion diagnosed cytologically was reactive lymphadenitis (41.3%) followed by tuberculous lymphadenitis in 38.7% cases. The different patterns of tuberculous lymphadenitis on microscopy were divided into four categories from I to IV with pattern I being the most frequently seen (53.5%). Conclusion: Our study highlighted the various morphological patterns of lymphadenopathy and the most common lesion diagnosed was reactive lymphadenitis. The present study found that FNAC is an effective screening tool for diagnosing benign and malignant lymphadenopathies and also to study the cytomorphological patterns in cases of tuberculous lymphadenitis. It reduces the need for surgical intervention and for the early diagnosis and management of patients with peripheral lymphadenopathy.